The Healthy Life Expectancy at Birth: A Comparison Study between Developed, Developing and Undeveloped Countries. - Khidir, Hewir; Etikan, İlker (Progress in Nutrition, 2021)
Life expectancy has always been taken into research since it is directly related to maintain human being extension. Many governmental organization and non-governmental foundation have studied the life expectancy in the countries and could be able to find some vital aspects which are factors to long the period of people life span. Studies found out that as long as there are good health care facilities, economic condition, high financial resource, security as nowadays becomes a serious problem and political status, the longer life may individual have it. In this study, we consider three different groups of countries for instance Developed Countries (France, Germany and The United Kingdome), Developing Countries (China, Malaysia and Brazil) and Undeveloped Countries (Ethiopia, Uganda and Haiti). Descriptive statistics and inferential statistics have carried out to compare the life exKeywords: Life Expectancy, Developed, Developing and Undeveloped Countries, Descriptive Statistics, Krusal-Wallis H and Mann-Whitney U